Tissue Engineering in Achilles Tendon Reconstruction; The Role of Stem Cells, Growth Factors and Scaffolds - Pillai, Dilip S.; S. Dhinsa, Baljinder; S. Khan, Wasim (Current Stem Cell Research & Therapy, 2017)
Background: Achilles tendon injuries are common, and present a challenge in the acute and chronic setting. There is significant morbidity associated with the injury and the numerous management strategies, as well as financial implications to the patient and the health service. To date, repair tissue from all methods of management fail to achieve the same functional and biomechanical properties as the native tendon. Objective: The use of tissue engineering technology may reduce morbidity, improve the biomechanical properties of repair tissue and reduce the financial burden. The goal is to produce completely integrated tendon repair tissue that has the functional and mechanical properties of the native tendon. This review evaluates the role of stem cells in tissue engineering for tendon reconstruction and the various sources for harvesting stem cells. Results: They can be obtained from the embryo, foetus or adult, and require the correct conditions for proliferation and differentiation. There remain many ethical concerns with the use of embryo or foetus harvested stem cells, thus the focus remains on adult sources, haematopoietic and non-haematopoietic. The improving knowledge of the role of growth factors is addressed, as is their effect on animal models for tendon repair. Growth factors include bone morphogenic proteins, transforming growth factor β, insulin-like growth factor and platelet derived growth factor. The role of scaffolds in human and animal models is reviewed, both naturally derived and synthetic scaffolds. Whilst numerous animal studies have reported encouraging results, further work is required. Conclusions: The ideal source of MSCs still has not been agreed upon, and little is known regarding the signalling pathways involved in tenogenesis of MSCs. Whilst current studies have shown encouraging results with regards to improved biomechanical and histological properties, further work is required to ascertain the growth factors, biomaterials and source of stem cells required for tendon regeneration.
Keywords: tissue engineering